New hope for the poor A perspective on the church in informal settlements in Africa - Verster, Pieter (UJ Press, 2012)
Empowering the poor remains an essential part of the Christian Gospel. The way in which the absolute poor in informal settlements in Africa can be empowered by the message of the Bible, needs to be researched. During research completed in informal settlements near Bloemfontein, Free State Province, South Africa, it has been established that the churches present in the situation are best equipped to relate to the poor and interpret the message of the Bible to them.